A Randomized Controlled Trial: Comparison of 4% Articaine versus 0.5% Bupivacaine for Ambulatory Orthopedic Surgery under Supraclavicular Block - Simon H. Armanious; Gamal A. Abdelhameed (Anesthesiology Research and Practice)
Background. Articaine has been used in many dental and ophthalmic outpatient procedures. In the era of ultrasound-guided regional techniques, we searched for short and potent local anesthetic for patients undergoing ambulatory upper limb procedures. However, studies about articaine efficacy in brachial plexus block are limited. In this study, we compared its safety and efficacy against bupivacaine as a commonly used anesthetic agent for ultrasound-guided supraclavicular brachial plexus block. Methods. This randomized prospective study was performed at Ain Shams University Hospital from January to March 2020. A total of 117 patients aged 20 to 60 years, with the American Society of Anesthesiologists physical status I and II, were enrolled in the study. Patients were randomly allocated into two groups: in group A, patients received 30 ml articaine 2%, and in group B, patients received 30 ml of bupivacaine 0.5%. We measured motor and sensory block duration as a primary outcome. Other secondary outcomes such as onset of block, duration of analgesia, patient satisfaction, and time to home discharge readiness were also measured. Results. We analyzed data collected from 97 patients. The motor block duration was significantly shorter in group A (165.73 ± 20.33 min) than in group B (220.27 ± 37.73 min). The onset of motor block was faster in group A (8.73 ± 4.33 min), and the postoperative VAS score was lower in group B. Patients in group A achieved an earlier home discharge of 289.67 ± 2.73 min. Conclusion. Earlier resolution of articaine block makes it more favorable than bupivacaine for ambulatory surgery. This trial is registered with (NCT04189198).